Exploring the impact of rebranding on stakeholders: a case study of Hotel Management School NHL Stenden - Anna Spenkelink; Rodney Westerlaken; Javed Suleri (Research in Hospitality Management, 2022)
The purpose of this study is to provide a better insight into the impact of rebranding on stakeholders; the case for this study is the rebranding of the Hotel Management School (HMS). This research has explored how the stakeholders have experienced rebranding and how the rebranding has affected the brand identity, image and loyalty. A qualitative research method was used and data was gathered conducting semi-structured, face-to-face interviews with the students, staff and industry partners. The data illustrates that due to effective internal communication the employees were not affected by the rebranding. Nevertheless, the brand identity, image and loyalty did not have the same effect on the students and industry partners. Thus, it is recommended that HMS pay more attention to improving the communication, rebuilding and expansion of the brand identity.